El control interno y su impacto en la gestión financiera de la Cooperativa de Ahorro y Crédito Juventud Unida Ltda en el cantón Guaranda provincia Bolívar en el periodo 2019-2020 - Colcha Puma, David Javier (2020)
This thesis work is focused on the need to propose an internal control manual for the Savings and Credit Cooperative Juventud Unida Ltda., Since it is an entity that does not have adequate internal control to achieve good financial management and Good level of participation in the financial market. An internal control manual has been prepared that will help the cooperative that has a good management in both the administrative and financial area, making known values, policies, strategies, positions and functions, and within it an internal control evaluation questionnaire as well ensure efficient and effective financial management of the cooperative. The thesis consists of three chapters in which different topics were studied according to the importance they reported to the study, this was limited to the descriptive, joint and mixed research of the Savings and Credit Cooperative Juventud Unida Ltda. In chapter one, everything about the framework where the referential, georential, legal and conceptual framework is made known. In chapter two, the research methodology is disclosed, which contains types of research, methods, techniques and research tools and information processing. In chapter three, the results and discussion of the research project are elaborated. This includes the fulfillment of objectives, the proposal of the internal control manual, conclusions and recommendations.